Chapter Isolation and molecular characterization of Fusarium species (Fungi, Ascomycota) from unhatched eggs of Caretta caretta in Tuscany (Italy) - Terracciano, Giuliana (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Caretta caretta is the only sea turtle species nesting along the Tuscan coastline, where nests are becoming more numerous and widespread, as well as the number of Sea Turtle Egg Fusariosis (STEF)-affected eggs. In this work, we analyzed eggs from natural nests of C. caretta that showed visual symptoms of STEF from Tuscan nests, with the aim to (i) isolate Fusarium spp. strains present in unhatched eggs, (ii) morphologically and molecularly characterize the isolated fungi and, finally, (iii) reconstruct the phylogenetic relationships between our isolates and those already known.